Hubungan Pengetahuan Ibu Tentang Faktor Resiko Persalinan Dengan Pemilihan Penolong Persalinan Di Bpm Zaitun Ernawati,Sst,Mm Di Pamekasan - Nova Purmahardini; Rohemah (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Aid deliveries are done by non-medical personel can lead to high MMR and IMR, so this requires the ability and skilss of the helper delivery so AKI can be avoided. The number of delievery assistance by a shaman due to many factors behind them, including education level, attitudes, perceptions, mother, and knowledge about risk factors of labor. The reality in the work area Pegantenan health centers in 2011 most of the thirs trimester pregnant women choose delivery assistance at the end of the healer. The research objective is to determine the relationship of maternal knowledge about risk factors for the selection of labor with delivery helper in the work area BPM Zaitun Ernawati pamekasan. The study design used in the analytic correlation with the type of cross sectional study. Population and sample in this study were three final trimester pregnant women with a large sample of 72 respondents. Sampling techniques using probability sampling methods with the type of cluster sampling. Coefficient of contingency analysis results with the help of SPSS software version 0,05 16.00with significant level retrieved significant value of 0,524 with 0,000. Because the Sig value 0,000 < 0,05 means there is relationship between the level of knowledge about risk factors for birth mothers with a selection of auxiliary labor. The role of health worker or midwife is very encouraging mothers to choose the delivery assistance to health care, by providing guidance counseling both individuals and groups through ANC visits, IHC, or through group Dasawisma and recitals.